Plotting Chart Indian Sector of Antarctica / Publication of the Office of the Chief of Hydographic Service of the Navy (USSR) - United States. Hydrographic Office (Washington, DC : U.S. Navy Hydrographic Office, 1959)
1st Edition, 1955. New Edtion, 1958. Reproduced by the U.S. Navy Hydrographic Office (November 1959) from U.S.S.R. chart Map in Russian and English.; Includes inset map.; "U.S.S.R. 339" -- margins Grayscale; 1:7,250,000